Physics of the soil medium organization part 2: pedostructure characterization through measurement and modeling of the soil moisture characteristic curves - ASSI, AMJAD T.; Braudeau, Erik F.; Accola, Joshua J.; HOVHANNISSIAN, Gaghik; Mohtar, Rabi (Frontiers in Environmental Science, 2014)
Accurate measurement of the two soil moisture characteristic curves, namely, water retention curve (WRC) and soil shrinkage curve (SSC) is fundamental for the physical modeling of hydrostructural processes in vadose zone. This paper is the application part following the theory presented in part I about physics of soil medium organization. Two native Aridisols in the state of Qatar named locally Rodah "räôd´ə" soil and Sabkha "săb′kə" soil were studied. The paper concluded two main results: the first one is about the importance of having continuous and simultaneous measurement of soil water content, water potential and volume change. Such measurement is imperative for accurate and consistent characterization of each of the two moisture characteristic curves, and consequently the hydrostructural properties of the soil medium. The second is about the simplicity, reliability, strength and uniqueness of identifying the characteristic parameters of the two curves. The results also confirmed the validity of the thermodynamic-based equations of the two characteristic curves presented in part I.